miRNAs in anti-cancer drug resistance of non-small cell lung cancer: Recent advances and future potential - Yan, Hang; Tang, Shengjie; Tang, Shoujun; Zhang, Jun; Guo, Haiyang; Qin, Chao; Hu, Haiyang; Zhong, Chuan; Yang, Li; Zhu, Yunhe; Zhou, Haining (Frontiers in Pharmacology, 2022)
Non-small cell lung cancer (NSCLC) is one of the most common malignant tumors worldwide. Clinical success is suboptimal owing to late diagnosis, limited treatment options, high recurrence rates, and the development of drug resistance. MicroRNAs (miRNAs), a range of small endogenous non-coding RNAs that are 22 nucleotides in length, have emerged as one of the most important players in cancer initiation and progression in recent decades. Current evidence has revealed the pivotal roles of miRNAs in regulating cell proliferation, migration, invasion, and metastasis in NSCLC. Recently, several studies have demonstrated that miRNAs are strongly associated with resistance to anti-cancer drugs, ranging from traditional chemotherapeutic and immunotherapy drugs to anti-vascular drugs, and even during radiotherapy. In this review, we briefly introduce the mechanism of miRNA dysregulation and resistance to anti-tumor therapy in NSCLC, and summarize the role of miRNAs in the malignant process of NSCLC. We then discuss studies of resistance-related miRNAs in chemotherapy, radiotherapy, targeted therapy, immunotherapy, and anti-vascular therapy in NSCLC. Finally, we will explore the application prospects of miRNA, an emerging small molecule, for future anti-tumor therapy. This review is the first to summarize the latest research progress on miRNAs in anti-cancer drug resistance based on drug classification, and to discuss their potential clinical applications.